2010
DOI: 10.4314/just.v30i2.60542
|View full text |Cite
|
Sign up to set email alerts
|

Energy Performance of Office Buildings in Ghana

Abstract: The parametrical measures that could improve the thermal performance of a sample of five existing buildings in Kumasi, Ghana were explored through a simulation application. These buildings are representative of the majority of existing low-rise office buildings in Kumasi and house different functions (university offices, private companies, municipal offices, etc.). The applied cooling systems typically involve split air-conditioning units. The simulation models were calibrated using indoor and external environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…With 43 per cent of the occupants using fans in their spaces and 35 per cent (Figure 8) indicating that their fans were efficient (effective and very effective), it goes without saying then that the fans could provide some respite for the occupants. According to the research, fans have been observed to reduce air temperature to an estimated 2°C (Koranteng, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With 43 per cent of the occupants using fans in their spaces and 35 per cent (Figure 8) indicating that their fans were efficient (effective and very effective), it goes without saying then that the fans could provide some respite for the occupants. According to the research, fans have been observed to reduce air temperature to an estimated 2°C (Koranteng, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Through purposive sampling, 225 students who are all residence of one of the three halls on KNUST campus were selected for the study. The Mahoney Tables were used to generate a set of reference tables as a guide to climate appropriate designs (Koranteng, 2010). The guidelines for entering data into the Mahoney Tables are presented and explained fully by many researchers (Xia, 2012; Koranteng, 2010; Upadhyay et al , 2006; Raydan and Melki, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, minimizing heat transfer through building envelope is crucial for reducing cooling load. The selection of building fabrics should be carefully considered to enhance their potential in minimizing heat and moisture transfer through building components for improved performance, and consequently, the energy and indoor environmental quality [8]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the building sector, the increased use of airconditioners, inefficient curtain walls and sliding windows, and the lack of sustainable design principles, especially in office buildings have contributed to the present energy situation (Koranteng, 2010). The overall energy performance of a window assembly is dependent not only on the glazing and frame materials themselves, but on a number of architectural and interior design decisions (Carmody et al, 2007).…”
Section: Introductionmentioning
confidence: 99%